Block copolymer brush layer-templated gold nanoparticles on nanofibers for surface-enhanced raman scattering optophysiology - Zhu, Hu; Spatz, Joachim P. (ACS applied materials & interfaces, 2019)
A nanothin block copolymer (BCP) brush-layer film adsorbed on glass nanofibers is shown to address the long-standing challenge of forming a template for the deposition of dense and well-dispersed nanoparticles on highly curved surfaces, allowing the development of an improved nanosensor for neurotransmitters. We employed a polystyrene-block-poly(4-vinylpyridine) BCP and plasmonic gold nanoparticles (AuNPs) of 52 nm in diameter for the fabrication of the nanosensor on pulled fibers with diameters down to 200 nm. The method is simple, using only solution processes and a plasma cleaning step. The templating of the AuNPs on the nanofiber surprisingly gave rise to more than 1 order of magnitude improvement in the surface-enhanced Raman scattering (SERS) performance for 4-mercaptobenzoic acid compared to the same AuNPs aggregated on identical fibers without the use of a template. We hypothesize that a wavelength-scale lens formed by the nanofiber contributes to enhancing the SERS performance to the extent that it can melt the glass nanofiber under moderate laser power. We then show the capability of this nanosensor to detect the corelease of the neurotransmitters dopamine and glutamate from living mouse brain dopaminergic neurons with a sensitivity 1 order of magnitude greater than with aggregated AuNPs. The simplicity of fabrication and the far superior performance of the BCP-templated nanofiber demonstrates the potential of this method to efficiently pattern nanoparticles on highly curved surfaces and its application as molecular nanosensors for cell physiology.
Gesehen am 24.10.2019